2014
DOI: 10.18632/oncotarget.1678
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia-related kinase 1 (VRK1) confers resistance to DNA-damaging agents in human breast cancer by affecting DNA damage response

Abstract: Vaccinia-related kinase 1 (VRK1) belongs to a group of sixteen kinases associated to a poorer prognosis in human breast carcinomas, particularly in estrogen receptor positive cases based on gene expression arrays. In this work we have studied the potential molecular mechanism by which the VRK1 protein can contribute to a poorer prognosis in this disease. For this aim it was first analyzed by immunohistochemistry the VRK1 protein level in normal breast and in one hundred and thirty six cases of human breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 52 publications
1
52
0
7
Order By: Relevance
“…Such an effect has already been identified in response to doxorubicin. 54 Alternatively, high VRK1 levels should make cells more resistant to treatment, and this has been reported in breast cancer, 54 in which VRK1 identifies a subgroup within estrogen receptor positive cases that presents a poorer prognosis. 64,65 The structure of VRK1 indicates that any specific inhibitor will have no crossinhibitory effect on other kinases due its very low promiscuity index 55,56 and, therefore, makes VRK1 a very good candidate for development of highly specific inhibitors that may be useful in treatment of some tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Such an effect has already been identified in response to doxorubicin. 54 Alternatively, high VRK1 levels should make cells more resistant to treatment, and this has been reported in breast cancer, 54 in which VRK1 identifies a subgroup within estrogen receptor positive cases that presents a poorer prognosis. 64,65 The structure of VRK1 indicates that any specific inhibitor will have no crossinhibitory effect on other kinases due its very low promiscuity index 55,56 and, therefore, makes VRK1 a very good candidate for development of highly specific inhibitors that may be useful in treatment of some tumors.…”
Section: Discussionmentioning
confidence: 99%
“…VRK1 is discovered as an early response gene and is one of the important factors for the initiation of cell division process, reflected on its overexpression in many cancerous tissues . Recent studies have shown direct correlation of poor clinical outcomes of breast cancer patients was associated with high expression levels of VRK1 suggesting it as a promising cancer drug target . VRK1 can phosphorylate itself (auto‐phosphorylate) as well as its interacting substrate proteins.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent studies have shown direct correlation of poor clinical outcomes of breast cancer patients was associated with high expression levels of VRK1 17 suggesting it as a promising cancer drug target. [16][17][18][19] VRK1 can phosphorylate itself (auto-phosphorylate) as well as its interacting substrate proteins. During mitosis, VRK1 can phosphorylate (a) barrierto-autointegration factor (BAF) to regulate the morphology of nuclear envelope 20 ; (b) H3's N-terminal tail H-15 N TROSY spectra of VRK1 in free state (red) with that of VRK1 in the presence of AMP-PNP at a molar ratio of 1:5 (VRK1: AMP-PNP; blue).…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, el desarrollo de inhibidores de diferentes componentes de la respuesta al daño en el ADN pueda tener un gran potencial para la sensibilización de las células a los tratamientos, en particular aquellos tipos de cáncer más radio o quimioresistentes (Curtin, 2012;Martin, 2001). Se ha demostrado que células de cáncer de mama positivas para el receptor de estrógenos muestran altos niveles proteicos de VRK1, lo que puede contribuir a la resistencia de este tipo de tumores (Salzano et al, 2014). De tal manera, proponemos a VRK1 como una diana de inhibición ya que hemos demostrado que esta quinasa tiene un papel importante en la modulación de la respuesta al daño en el ADN a diferentes niveles en la vía de señalización, de tal forma que un tratamiento combinado puede ser una alternativa a producir lesiones sin que estas puedan ser reparadas, por ejemplo la inhibición de ATM con inhibidores específicos como KU55933 o CGK733, junto con el tratamiento con doxorubicina, incrementaron los niveles de apoptosis en células cancerosas (Khalil HS, 2012).…”
Section: Rnf8unclassified